THE SOUND CORRESPONDENCE OF TEOCHEW, HAKKA, AND CANTONESE - Novita, Sherly; Widayati, Dwi; Tarigan, Bahagia (Faculty of Humanities, Diponegoro University, 2020)
This research is based on a theory in Historical Comparative Linguistics. This theory is also called a diachronic theory, which involves the analysis of the form and regularity of changes in common languages such as those accompanied by sound changes. The objects of the research are Teochew (TC), Hakka (HK), and Cantonese (CO) dialects used in Medan city. These three dialects are categorized into the Sino-Tibetan family. Sino-Tibetan (ST) as one of the largest language families in the world, with more first-language speakers than even Indo-Europeans, is having more than 1.1 billion speakers of Sinitic (the Chinese dialects) constitute the world's largest speech community. According to STEDT (Sino-Tibetan Etymological Dictionary and Thesaurus), Chinese is considered as a Sino-Tibetan language family. The research method used is the qualitative method. The data collection method and technique used to refer to the conversation method with the techniques of recording and writing. The data were analyzed using the qualitative method of glottochronology. The result of the research shows that TC, HK, and CO were related in terms of sound correspondences and were separated thousands of years ago. TC and HK were related and both corresponded identically one similar vowel, one similar consonant, and one different phoneme, and one similar syllable. TC and CO were related and both corresponded to one similar vowel, one similar vocalic cluster, one similar consonant, and one different phoneme, and one similar syllable. HK and CO were related and both corresponded identically, one similar vowel, one similar consonant, one different phoneme, one different vocalic cluster, and one similar syllable. From all the findings and discussion in this research, the writer has concluded that HK and CO are the closest dialects among the three compared dialects.